Investigation and Validation of Mission Evaluation Models for Space Close-Range Inspection - Jianyong Zhou; Zhipu Hou; Kebo Li (International Journal of Aerospace Engineering)
Space close-range inspection can be used to carry out close-range observation and monitoring of targets for identifying the target’s types and working states, which is of great significance for space missions such as in-orbit services. The effectiveness evaluation of space inspection tasks will significantly affect the studies on the trajectory design, orbit motion control, and task termination conditions. However, the evaluation models in previous studies are too simple such as that they are usually without considering dynamic changes in the satellite orbit relative motion. Besides, these studies fail to build a comprehensive evaluation model for the whole inspection task process. In this paper, taking the most commonly used optical inspection as an example, the novel multifactor inspection task effectiveness evaluation models were investigated, including the constraint models of observation, the relative distance evaluation model, the effective observation time evaluation model, and the target observation angle evaluation model. These models solve the effectiveness evaluation problem for the complete process of an inspection task, which can support the design of inspection strategies and trajectories better by using the evaluation results. In addition, numerical simulations and 20 semiphysical experiments were carried out to validate the proposed evaluation models.